Modulation of the inflammatory response by taurine and its structural analogue, HEPES - Brennan, Cara (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2000)
Activated neutrophils (PMNs) have been implicated in the production of tissue injury in inflammatory-bowel disease (IBD) through release of proinflammatory mediaters during respiratory burst activity. Taurine, the most abundant free β-amino acid in human PMNs possesses anti-inflammatory properties. HEPES, a structural analogue of taurine is a potent anti-inflammatory agent in vivo. Experiments on the effects of taurine and HEPES on PMN function in vitro revealed that these compounds prevent receptor-mediated influx of Ca2+, decrease NADPH oxidase and respiratory burst activity and modulate adhesion. In contiast, Upon stimulation by soluble stimuli, taurine and HEPES increase NADPH oxidase activity, MPO activity and respiratory burst activity. The differential effects of taurine and HEPES on respiratory burst activity are most likely due to the biphasic effects of taurine and HEPES on Ca2+. IBD is characterised by increased NO with the potential to modulate apoptosis within the colon. It was demonstrated that exogenously-added NO induced PMN apoptosis. Taurine decreased nitrite generation in PMNs cultured with an exogenous source of NO without affecting apoptosis. HEPES increased endogenous NO production in fMLP-activated PMNs without affecting PMN apoptosis. Activated colonic epithelial cells cells, Caco-2 and HT-29 released large amounts of NO in response to LPS/IFN- γ in vitro. Endogenously produced NO induced apoptosis in the HT-29 colonic epithelial cell line which retains a p53 allele. In contrast, LPS/IFN- γ increased apoptosis in the Caco-2 cell line through a p53/NO-independent mechanism. Supplementation with taurine or HEPES did not significantly protect against LPS/IFN- γ-activated apoptosis in colonic epithelial cells. Experimental colitis resulted in an influx of PMNs into the colon with enhanced ROS activity and increased colonic nitrite generation. HEPES caused a significant reduction in tissue injury as assessed by a colon macroscope score. The administration of taurine decreased expression of the PMN adhesion receptor, CD11b/CD18 but did not decrease tissue injury in vivo. HEPES modulates the inflammatory response through a direct interaction with the respiratory burst pathway. The effectiveness of HEPES but not taurine on tissue injury in this rat experimental model of colitis may be explained by the ability of HEPES to be retained in the systemic circulation for longer periods of time than taurine. The efficacy of HEPES as a pharmacological agent demonstrated by this study suggest the future use of HEPES as an anti-inflammatory agent.
Keywords: Biochemistry, Ph.D.; Ph.D. Trinity College Dublin